PERBEDAAN EFEKTIVITAS ANTARA MEMBACA DENGAN MENDENGARKAN SURAH AL FATIHAH TERHADAP SKOR HALUSINASI - Ila Rifatul Mahmuda; Jumaini Jumaini; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Schizophrenia is a syndrome that can affect brain, so that it can cause several symptoms. One of the positive symptoms is hallucination. Controlling hallucination can be done with one of the modality therapies, psycho-religious therapy. One of the psycho-religious therapy that can be used is with the Al-Qur'an media especially Surah Al Fatihah. This research aimed to determine the differences effectiveness between reading and listening to Surah Al Fatihah toward hallucination score. This research used pre-post design with two comparison treatments. The sample of this research were 31 respondents who were divided into 16 respondents of reading groups and 15 respondents of listening groups taken based on the inclusion criteria using purposive sampling technique. Each experimental group was given an intervention for 6 consecutive days. The measurement instrument used is the Auditory Hallucination Rating Scale (AHRC), which has been standardized. The analysis that used is univariate analysis by using Dependent sample T-test and bivariate analysis using Independent sample T-test. The statistical result got p-value (0.652) > (α = 0.05) so it can be concluded that there is no significant differences between reading and listening to Surah Al-Fatihah toward hallucination score. Therefore, the intervention of reading and listening to Surah Al Fatihah can be done because both can decrease the hallucination score. Keywords: Hallucination score, listening of Al Fatihah, reading of Al Fatihah